If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 24 = 9x + -16 Reorder the terms: 24 + 5x = 9x + -16 Reorder the terms: 24 + 5x = -16 + 9x Solving 24 + 5x = -16 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 24 + 5x + -9x = -16 + 9x + -9x Combine like terms: 5x + -9x = -4x 24 + -4x = -16 + 9x + -9x Combine like terms: 9x + -9x = 0 24 + -4x = -16 + 0 24 + -4x = -16 Add '-24' to each side of the equation. 24 + -24 + -4x = -16 + -24 Combine like terms: 24 + -24 = 0 0 + -4x = -16 + -24 -4x = -16 + -24 Combine like terms: -16 + -24 = -40 -4x = -40 Divide each side by '-4'. x = 10 Simplifying x = 10
| 19.00=1.50 | | g(-2)=5x-1 | | 3x-197=15x+75 | | 5x+(-7)=4x-3 | | x^(1/2)*x^(1/2) | | 24x^2+4x-30x-5= | | 5*7=X*1092 | | -2x+3y-4y+5y= | | 12y+6(5)-4=7y | | 21c+5d(1-c)-cd= | | 13+8x=3(3x+2) | | 6w=27 | | 10x+5-3x+9=-11x+6x+38 | | T-20=-2 | | 0.75k+16=2-0.25 | | g(-3)=5x-1 | | 8(1.093x+1)=12 | | -7(3x-8)+2=-21x+58 | | 6(6x-7)=354 | | 3x+(-2)=2x+1 | | x=-2.5x+32.5 | | 5w+16=76 | | 5-(3x-2)-x-3=-4(4x+5)+13 | | 26=j-24 | | 48-19-29-51= | | 17+840=22x+760 | | 3x+(-7)=8x | | 6x-2=6(x+4) | | 14=w/2-11 | | x=-2.5x | | n-17=-17 | | 6y+12=-2-4 |